Comparison of the Practical and Theoretical Knowledge of the Hepatitis B Virus among Dental Hygiene Students - Sinan Yasin Ertem; Sertac Ozdogan; Ayla Ozturk; Ozge Akcam (치위생과학회지, 2020)
Background: Hepatitis B is an important public health problem as one of the leading causes of morbidity and mortality. The aim of this study was to compare the theoretical and practical knowledge levels of dental assistant students about Hepatitis B Virus.Methods: The 1st and 2nd grade students of the Oral and Dental Health program were invited to participate in the survey. Out of the 68 invited students, 61 completed the questionnaire. The average ages of the male and female students surveyed were 20.27±1.45 and 19.56±1.16, respectively. A total of 34 questions were asked, of which 15 measured basic theoretical knowledge and 19 assessed basic practical knowledge.Results: There was no statistically significant difference between the students’ knowledge for each question according to their sex and grade. When the questionnaire was grouped into basic theoretical and basic practical knowledge levels, both were observed to be high. While the lowest correct answer rate was 35.00% for the questions about practical applications, it was 31.14% for the questions measuring the level of theoretical knowledge. There was no statistically significant difference when the levels of knowledge of 1st and 2nd grade students were compared. Students answered the majority of the questions correctly, and ranged between 71% and 100%.Conclusion: Students’ high level of basic theoretical knowledge can be a result of their in-class education on the fundamentals. However, their knowledge about the correct approaches in practical applications indicates the beneficial role of having well-defined criteria and prevention protocols that are required in hospitals and the effectiveness of their environmental orientations.